International Capital Crunches : The Time-Varying Role of Informational Asymmetries - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2002)
We examine the determinants of capital flows to four developing countries during the 1990s using an explicitly disequilibrium econometric framework in which the supply and demand for capital are not necessarily equal and the actual amount of the flow is determined by the 'short side' of the market. We are thus able to detect instances of 'international capital crunch'-where capital flows are curtailed because of supply-side rationing-and to relate these instances to movements in the underlying fundamentals. The analysis highlights the role of asymmetric information-as distinct from the traditional concern with default risk-in conditioning capital flows.